Lysis Timer: a new sensitive tool to diagnose hyperfibrinolysis in liver transplantation. Issue 1 (3rd October 2018) - Roullet, Stéphanie; Labrouche, Sylvie; Mouton, Christine; Quinart, Alice; Nouette-Gaulain, Karine; Laurent, Christophe; Freyburger, Geneviève
Abstract : Aims: Diagnosis of hyperfibrinolysis in orthotopic liver transplantation (OLT) remains challenging. Euglobulin clot lysis time (ECLT) is not adapted to clinical situations. ROTEM is specific but seldom sensitive to hyperfibrinolysis. The Lysis Timer assesses 'Global Fibrinolytic Capacity' in citrated plasma (GFC/LT). GFC/LT associates reagents for in vitro triggering of the clot (thrombin and calcium) and its lysis (tissue-plasminogenactivator (t-PA)), turbidity signal acquisition by the Lysis Timer, and dedicated software converting the digital signal into an optical curve. A visual check of the curves was systematic to ascertain the lysis time values calculated by the software. The primary aim of this prospective observational study was to evaluate the ability of GFC/LT to recognise hyperfibrinolysis during OLT. The secondary aim was to compare its results with ROTEM maximum lysis (EXTEM ML) and with standard laboratory tests. Methods: Thirty consecutive adult patients undergoing OLT were included (NCT03012633 ). Standard laboratory tests, ROTEM, GFC/LT, ECLT and fibrinolysis parameters were assayed at five sample times. Results: GFC/LT was correlated with ECLT, plasmin activator inhibitor 1 antigen and activity and t-PA activity (r=0.490, 0.681, 0.643 and –0.359, respectively). Hyperfibrinolysis was defined as ECLT ≤60 min. Receiver operating characteristic curve analysis showed that GFC/LT with a threshold of 31 min detected hyperfibrinolysis with a sensitivity of 0.88 (95% CI 0.73 to 0.96), a specificity of 0.68 (95% CI 0.56 to 0.78) and an area under the curve (AUC) of 0.85 (95% CI 0.74 to 0.94). EXTEM ML >12% did not detect hyperfibrinolysis (sensitivity 0.38 (95% CI 0.24 to 0.55), specificity 0.95 (95% CI 0.86 to 0.99) and AUC 0.60 (95% CI 0.46 to 0.75)). Conclusions: GFC/LT recognised hyperfibrinolysis during OLT with a significant agreement with the other tests of fibrinolysis. Trial registration number: NCT03012633 .